The Effect of Perceived Value Using the Gamification Program on Customer Loyalty through Customer Satisfaction as an Intervening Variable (Study on Dana E-Wallet Application Users) - Chandra Deri Andika; Mahrinasari; Dwi Asri Siti Ambarwati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The tight competition of e-wallets in Indonesia requires DANA to continue to innovate in order to maintain the loyalty of its customers. One of these innovations is by providing value to customers through the application of gamification in the DANA application. On the other hand, although there is great hope that gamification can increase loyalty, researchers from Gartner stated that gamification tends to fail due to poor implementation. In DANA's own gamification program, many customers complain due to the current rules applied. This study aims to determine whether DANA's gamification program can create satisfaction as well as loyalty of its customers. The number of samples in this study were 100 respondents aged over 17 years, where the respondents were DANA users and had participated in the DANA Surprize program. Sampling was done using purposive sampling technique. The data analysis process was carried out using PLS with SmartPLS software version 4.0.9.2. Overall this research resulted in: (1) Hedonic, utilitarian, and social values in gamification affect customer satisfaction, (2) Customer satisfaction affects customer loyalty, (3) Hedonic values in gamification affect customer loyalty, while utilitarian and social values in gamification have no effect on customer loyalty, (4) Customer satisfaction mediates the relationship between hedonic, utilitarian, and social values in gamification to customer loyalty.